The possibility of allogeneic placental therapy of postovariectomical manifestations in patients with gynecological cancer after antitumor treatment - L V Pokul; M R Orazov; M G Lebedeva; T N Bebneva; S R Polikarpova (IP Berlin A.V., 2017)
The results of a clinical-psychological prospective examination of 131 patients with cervical cancer, the uterus body and ovaries of stage I-III according to FIGO, reproductive age in total hysterovectomy and radiation suppression of ovaries isolated in three clinical groups are presented: group I - patients after combined and complex special treatment; Group II - patients after combined radiation treatment and group III - patients after combined and complex treatment, therapy of postovariochemical manifestations of which was carried out by traditional therapy. Identification of personal resources of stress-resistance was carried out using the copy-test of R.Lazarus. The intensity of oxidative processes in blood plasma was judged by the content of their carbonyl derivatives, revealed in the reaction with 2,4-dinitrophenylhydrazine. Results and discussion. For patients in the state of total hysterovarioectomy (groups I and III), the hyperactivity of the strategy "Confrontation" (76.8% and 76.4%, respectively) and "Positive revaluation" (67.8% and 72.6%) are a common phenomenon. "Constructive strategies"; "Distant" (73.8%) and "Acceptance of responsibility" (82.5%) are typical for patients of the II group who are in drug and radiation suppression. In the blood of all patients, increased oxidative potential was determined. Significant changes were demonstrated in the analysis of the intensity of induced (metal-catalyzed) OMB: at λ 370 nm and λ 530 nm in group I and group III (p